Porphyromonas gingivalis Placental Atopobiosis and Inflammatory Responses in Women With Adverse Pregnancy Outcomes - Gómez, Luz Amparo; De Avila, Juliette; Castillo, Diana Marcela; Montenegro, Daniel Antonio; Trujillo, Tammy Gorety; Suárez, Lina J.; Lafaurie, Gloria Inés (Frontiers in Microbiology, 2020)
The microbiome modulates inflammation at the fetal maternal interface on both term and preterm labor. Inflammophilic oral bacteria, such as Porphyromonas gingivalis, as well as urogenital microorganisms could translocate to the placenta and activate immune mechanisms in decidual tissue that are associated with adverse pregnancy outcomes. This study establishes the associations between the presence of microbes in the placenta and placental cytokine patterns in women who presented adverse pregnancy outcomes, e.g. low birth weight (LBW), preterm premature rupture of membranes (PPROM), preterm birth (PTB) and other clinical signs related to Chorioamnionitis. A total of 40 pregnant women were included in the study and divided into five groups according to placental infection (PI) and adverse pregnancy outcomes (APO), as follows: (1) women without PI and without APO ( n=17), (2) women with P. gingivalis-related PI and APO (n=5), (3) women with P. gingivalis-related PI and without APO (n=4), (4) women without PI with APO (n=9), and (5) women with PI related to urogenital microorganisms and APO (n=5). Obstetric, clinical periodontal status evaluation, and subgingival plaque sampling were performed at the time of delivery. Placental levels of interleukin IL-1β, IL-6, IL-10, IL-15, IL-17A, IL-17F, IL-21, IL-12p70, tumor necrosis factor-α (TNF-α), monocyte chemoattractant protein-1 α (MCP-1α), granzyme-B, and interferon-γ (IFN-γ) were determined using a multiplex flow cytometry assay. All patients showed a predominant Th-1 cytokine profile related to labor, characterized by IFN-γ overexpression. The analysis by groups suggests that Th-1 profile was trending to maintain cytotoxic cell activity by the expression of IL-15 and granzyme-B, except for the group with P. gingivalis-related PI and APO, which exhibited a reduction of IL-10 and IL-17F cytokines (p< 0.05) and a Th-1 profile favoring macrophage activation by MCP-1 production (p< 0.05). This study confirms a pro-inflammatory pattern associated with labor, characterized by a Th-1 profile and the activity of cytotoxic cells, which is enhanced by placental infection with urogenital microorganisms. However, PI associated with P. gingivalis suggests a switch where the Th-1 profile favors an inflammatory response mediated by MCP-1 and macrophage activity as a mechanistic explanation of its possible relationship with adverse outcomes in pregnancy.